Estrutura familiar e rendimentos do trabalho dos ricos - Marcelo Medeiros (Universidade do Estado do Rio de Janeiro, 2004)
Fair redistributive measures require better knowledge of who the rich are. In order to evaluate the extent to which individuals are rich because they enjoy a differentiated family structure, this study tests three hypotheses concerning inequalities between the rich and the non-rich, relating the advantage of the rich to: a peculiar demographic structure (fertility levels, position in the life cycle, etc.); higher employment and greater yield of available labor (workforce participation and employment rates, length of workday); or occupation of better positions in the work market (higher remuneration). The hypothesis testing is based on a breakdown of families' per capita income, using data from the Brazilian National Household Sample Surveys (PNADs) from 1997, 1998, and 1999. The results suggest that the existence of a wealthy elite in the country is explained mostly by inequalities in workers' remuneration rather than by the population's demographic profile or by the workforce participation and employment rates for workers from the various families.